Godność dziecka – odkrywana, zdobywana, niszczona - Smolińska- Theiss, Barbara (Horyzonty Wychowania, 2017)
Dignity – engraved in every man’s nature – demands affirmation all the stronger the more person is threatened in his basic and inalienable rights. This threat makes itself felt in particular periods of human life, it certainly refers to childhood. Child’s dignity was „discovered” at a relatively late stage of development of Western societies. At the same time, the history of the past one hundred years can be deciphered as the time of trampling on child’s dignity as a result of the dominance of totalitarian systems. Both fundamental sources of threat to child’s dignity lie in the sphere of social communication, where because of the mass media child is reduced to the consumer of impressions, which is why his natural world becomes impoverished. Similarly, in socio- economic dimension childhood is threatened due to the progress of marginalisation processes affecting more and more Polish families. The text constitutes a starting point for pedagogical survey orientated around the concept of child’s dignity. In this sense, it emerges either as an epistemological category, whose application will allow for clarification and description of the peculiar character of childhood, or as an object of axiological reflection considering man’s relations with transcendental reality.